Practices and beliefs among Malaysian dentists and periodontists towards smoking cessation intervention - Vaithilingam, R.D.; Noor, N.M.M.; Mustafa, R.; Taiyeb-Ali, T.B. (Penerbit Universiti Kebangsaan Malaysia, 2012)
This study compared the attitudes, practices and perceived barriers among Malaysian dentists and periodontists towards smoking cessation interventions (SCI) for patients. A self-administered questionnaire, which covered respondents beliefs, practices as well as barriers and limitations towards SCI, were posted to 289 dentists from four Malaysian states and 35 Malaysian periodontists. In all, 236 (82) dentists and 26 (80) periodontists responded. More periodontists than dentists routinely record patient's smoking status at first visit (89.3 vs 19.1) (pp<0.001), recommend nicotine replacement aids (37 vs 16.3) (p=0.031), refer to smoking cessation clinics (40.7 vs 14) (p=0.001), followed-up smoking cessation with patients (70.4 vs 11.3) (pp<0.001) and described themselves as being committed to patients' SCI (81.5 vs 53.4) (p=0.013). Limitations faced by dentists as compared to periodontists in SCI were due to insufficient time (pp<0.001) and fear it will affect dentist-patient relationship (p=0.034). The findings in this study emphasize the importance of SCI and the need for further training in SCI among Malaysian periodontists and government dentists. Copyright Reserved Â© 2007 Sains Malaysiana.